2006
DOI: 10.1097/01.mlr.0000233679.20898.e9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Outcomes of Nonadherence to Highly Active Antiretroviral Therapy in Patients With Human Immunodeficiency Virus

Abstract: Typical adherence with HAART reduces quality-adjusted life expectancy by 12% compared with ideal adherence. Interventions to improve adherence appear to be a highly cost-effective use of resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 43 publications
2
36
0
3
Order By: Relevance
“…One large retrospective study found that high rates of medication adherence were associated with lower disease-related medical costs and significantly lower hospitalization rates for patients with diabetes, hypertension, hypercholesterolemia, and congestive heart failure [10]. Similar relationships were observed when adherence and health care costs were analyzed in patients with HIV [11] and osteoporosis [12].…”
Section: Introductionmentioning
confidence: 74%
“…One large retrospective study found that high rates of medication adherence were associated with lower disease-related medical costs and significantly lower hospitalization rates for patients with diabetes, hypertension, hypercholesterolemia, and congestive heart failure [10]. Similar relationships were observed when adherence and health care costs were analyzed in patients with HIV [11] and osteoporosis [12].…”
Section: Introductionmentioning
confidence: 74%
“…Nonadherence is an important predictor for losing the long-term clinical and economic benefits of ART. Munakata et al 12 reported that nonadherence with treatment reduced the expected clinical benefits of ART by 12%. Our results suggest that interventions improving adherence to ideal levels also have great potential for economic benefit, especially in developing countries without alternative treatment regimens.…”
Section: Adherence and Medical Costmentioning
confidence: 99%
“…10 Other positive outcomes related to ART, including decreased hospital readmissions and reduced cost, have been described by some western studies. 11,12 Published literature regarding adherence to ART and treatment outcomes among Chinese HIV=AIDS patients is limited. Two current studies have assessed the levels of adherence to ART and associated factors in Chinese populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that young adults have poorer rates of retention in care than older adults, suggesting that young adults are more at risk for being lost to follow-up. 6,7 For HIV-positive patients, adherence to ART to the point of viral suppression can lower the risks of disease progression and death, 8,9 reduce overall health care costs, 10 and, potentially, decrease HIV transmission. 11 Despite improvements in ART regimens with regard to dosing frequency, dosing constraints (i.e., food restrictions), storage conditions, and adverse effects, 12 drug adherence remains a significant problem.…”
Section: Introductionmentioning
confidence: 99%